Exploring opportunities of Artificial Intelligence in aquaculture to meet increasing food demand - Mohd Ashraf Rather; Ishtiyaq Ahmad; Azra Shah; Younis Ahmad Hajam; Adnan Amin; Saba Khursheed; Irfan Ahmad; Showkat Rasool (Food Chemistry: X, 2024)
The increasing global population drives a rising demand for food, particularly fish as a preferred protein source, straining capture fisheries. Overfishing has depleted wild stocks, emphasizing the need for advanced aquaculture technologies. Unlike agriculture, aquaculture has not seen substantial technological advancements. Artificial Intelligence (AI) tools like Internet of Things (IoT), machine learning, cameras, and algorithms offer solutions to reduce human intervention, enhance productivity, and monitor fish health, feed optimization, and water resource management. However, challenges such as data collection, standardization, model accuracy, interpretability, and integration with existing aquaculture systems persist. This review explores the adoption of AI techniques and tools to advance the aquaculture industry and bridge the gap between food supply and demand.